Sentiment Analysis towards the 2024 Vice Presidential Candidate Debate Using the Support Vector Machine Algorithm - Harahap, Raihan Rizieq; Furqan, Mhd. (Sinkron : jurnal dan penelitian teknik informatika, 2024)
In today’s digital era, social media plays an important role in disseminating information and influencing public opinion. For instance, YouTube. At the 2024 Vice Presidential Debate, YouTube became a medium where people gave various comments. This study aimed to analyze public sentiment through comments on the 2024 Vice Presidential Debate on the Metro TV YouTube channel. This study used descriptive quantitative methods with the Support Vector Machine algorithm to identify various public comments. The results show that from the data experiment taken as many as 1012 data, 80% data training amounting to 809 data and 20% data testing amounting to 203 data is carried out. An accuracy of 82% was obtained with a precision value of 80%, a recall value of 87%, and an f1-score value of 83%. With a fairly high accuracy value, the support vector machine model can be said to be the right model to calculate the accuracy value in sentiment analysis.